Sensing UMTS bands using cyclostationary features and cooperation between opportunistic terminals - Marques, P. (2012)
The Opportunistic Radio (OR) concept relies on the cognitive features of the OR terminals, namely the ability to adapt its transmitter parameters, based upon interaction with the RF environment in which it operates. An OR system operates in licensed frequency bands, exploiting opportunities and operating with a lower priority regarding the licensed system, implementing a spectrum pool mechanism. The most important constraint is that the OR network should always avoid harmful interference with the licensed system, therefore it should reliably detect licensed signals in the used band in order to avoid interfering with the licensed owner of that band. Given the importance of UMTS systems in current wireless communications, this paper is focused on 3G bands and addresses the problem of sensing weak UMTS signals. The proposed sensing algorithm exploits the cyclostationary features of UMTS signals and the cooperation between multiple OR terminals clustered in the OR network.